Opposing trends in winter Atmospheric River over the Western and Eastern US during the past four decades - Wenhao Dong; Ming Zhao; Zhihong Tan; V. Ramaswamy (npj Climate and Atmospheric Science)
Abstract Winter atmospheric rivers (ARs) are crucial for water supply and extreme weather events over the western (WUS) and eastern US (EUS), yet their long-term trends and interplay remain unclear. Here we fill this gap by analyzing multiple observational AR products over the past four decades. Contrasting yet interrelated trends emerge in AR frequency, intensity, and associated mean precipitation. A decline in AR activity over WUS contributes to a drying trend, while notable increases over EUS foster a wetter climate. These trends are driven by large-scale atmospheric and oceanic variability in the Pacific, which strengthens anticyclonic circulation patterns near both coasts. These anticyclonic patterns, however, have opposing effects–impeding ARs from steering to WUS while facilitating their development over EUS. Our findings present a unified explanation for the observed AR trends and have co-beneficial implications for mitigating concerns related to AR-induced extreme events across both densely populated coastal regions.